Awareness, perceptions and use of snus among young adults from the upper Midwest region of the USA. Issue 6 (20th July 2012) - Choi, Kelvin; Forster, Jean
Abstract : Background: Since its introduction in 2006, snus has been aggressively marketed by tobacco companies. However, little is known about the awareness, perceptions and use of snus among young adults after Camel and Marlboro snus were sold nationwide in 2010. Methods: Data were collected from 2607 young adults (ages 20–28) who participated in the Minnesota Adolescent Community Cohort Study in 2010–2011. Data include awareness of snus, ever and past 30-day use, perceived potential of snus as a quit aid, and perceived harmfulness and addictiveness of snus relative to cigarettes. The authors assessed the associations between these outcome variables and socio-demographic characteristics. Results: Overall, 64.8% of participants were aware of snus, 14.5% ever used snus and 3.2% used snus in the past 30 days. Men and participants who smoked >100 cigarettes in their lifetime were associated with these three outcomes (p<0.05). Among those who were aware of snus, 16.3% agreed snus can help people quit smoking, 17.3% agreed snus is less harmful than cigarettes and 11.3% agreed snus is less addictive than cigarettes. These perceptions were associated with ever use and the past 30-day use of snus (p<0.05). Conclusions: In this regional sample of US young adults, the majority of young adults were aware of snus, and over one in 10 had used snus. More young adults in the sample than the overall US adult population believed that snus is less harmful than cigarettes. Perceptions of snus are associated with snus use. Strategic health communication interventions targeting young adults to confront the positive perceptions associated with snus may be needed to curb the interest in snus.